Pengaruh Jumlah Lubang Distributor Terhadap Unjuk Kerja Fluidized Bed Gasifier - Setyawan, Didik, NUR AKLIS,ST,M.Eng (2017)
With the depletion of reserves and production of oil and gas (oil & gas), while the demand for fuel oil and natural gas increased from year to year, so need to look for other alternative energy reserves that are friendly to the environment. Now developed research with rice husk biomass raw materials to be transformed into new fuel. The purpose of this research is to know the influence of the number of holes against distributor fluidized bed gasifier performance, to know the minimum speed of fluidization, to find out the temperature of the reactor, to know the old boiling water, to find out the temperature of the fire. In this study using a variation of the air distributor with the respective number of holes 19.28 and 37. Retrieve data with a composition of 2 kg of rice husk and blend each 0.5 kg of silica sand and limestone, include fluidization the minimum speed, temperature reactor, temperature, fire point, temperature of water boiled with 1 liter of water boil, the recording data every 2 minutes. The results showed a variation of air distributor with a total of 19 holes obtained highest reactor temperature of 331,7°C, flame time effectively for 60 minutes. Long boiling water for 18 minutes and the temperature point of the highest fire of 446,3°C. Air distributor with a variation of the number of holes of the highest temperature of the reactor obtained 28 of 460,9°C, flame time effectively during 56 minutes. Long boiling water for 16 minutes and the temperature point of the highest fire of 482,7°C. Air distributor with a variation of the amount of 37 holes obtained the highest of reactor temperature 495,4°C, flame time effective for 50 minutes. Long boiling water for 12 minutes and the temperature point of the highest fire of 532,9°C.